The Implementation of The Health Protocol Policy in Preventing the Dissemination of COVID-19 in Minimarkets, Indonesia - Ria Irianti; Jasmin Ambas; Andi Rizki Amelia; Rezky Aulia Yusuf (STRADA : Jurnal Ilmiah Kesehatan, 2021)
This study aimed to investigate the implementation of the COVID-19 prevention guidelines among minimarkets at Makassar City, South Sulawesi. This is a qualitative study. Data were collected using a semi-structured questioner. Total 11 informants participated; they were minimarket managers, staff, consumers, and the COVID-19 task forces. The data were analyzed using NVivo. The application of regulation Number HK.01.07 /Menkes/382/2020 concerning health protocols for the public in public places and facilities to prevent and control coronavirus disease 2019, we found that most of the minimarkets have implemented health protocols, especially in washing hands with soap. In addition, although the application of social distancing during the visit (transaction) process at minimarkets has not been maximized due to crowded conditions and narrow locations. This study, therefore, suggests the need for the health authorities to proactively sensitize those involved in the implementation of COVID-19 measures on the importance and mechanisms of implementing health protocols